2001
DOI: 10.1097/00000658-200104000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Sentinel Node Mapping in Carcinoma of the Colon and Rectum

Abstract: ObjectiveIncreasing evidence supports that the sentinel node (SN) is at greatest risk for harboring metastatic disease. This study describes a novel technique to identify the SN in colorectal carcinoma. MethodsWithin 30 minutes of resection, colorectal specimens were injected submucosally with isosulfan blue in four quadrants. Blue lymphatic channels were identified in the mesentery and followed to the blue-stained SN(s), which were then harvested. The specimen was fixed in formalin and subsequently analyzed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0
10

Year Published

2002
2002
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(95 citation statements)
references
References 40 publications
3
82
0
10
Order By: Relevance
“…In vivo and ex vivo methods have been developed, but it seems necessary to combine this technique with advanced methods like immunohistochemistry or PCR to demonstrate an advantage in comparison to conventional dissection. [19][20][21] Therefore, it is questionable if these interesting techniques will find usage beyond specialized centers.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo and ex vivo methods have been developed, but it seems necessary to combine this technique with advanced methods like immunohistochemistry or PCR to demonstrate an advantage in comparison to conventional dissection. [19][20][21] Therefore, it is questionable if these interesting techniques will find usage beyond specialized centers.…”
Section: Discussionmentioning
confidence: 99%
“…The principle applies not just to cutaneous melanoma but to breast cancer, 3 Merkel cell cancer, 16 squamous carcinoma of the skin and vulva and tumors of the gastrointestinal tract. 4,5 The position of the sentinel node is determined by the course of the lymphatics that drain the body site of the primary tumor rather than the fixed anatomic position of individual node(s) relative to the primary tumor. It is necessary to use a visible dye and/or radioactive marker to highlight the relevant afferent lymphatics and the lymph node that is their destination.…”
Section: Discussionmentioning
confidence: 99%
“…2 In the absence of distant metastases, the presence or absence of lymph node metastases appears to be the most important prognostic factor in patients with colorectal carcinoma. 3 Furthermore, the lymph node status is the primary determinant for adjuvant therapy after surgical resection. Randomized clinical trials have demonstrated a survival benefit for patients with Stage III colorectal carcinoma using 5-flurouracil and leucovorin.…”
Section: Methodsmentioning
confidence: 99%